Disequilibrium Rheology and Crystallization Kinetics of Basalts and Implications for the Phlegrean Volcanic District - Kolzenburg, Stephan; Hess, Kai-Uwe; Berlo, Kim; Dingwell, Donald B. (Frontiers in Earth Science, 2020)
Large volcanic eruptions are frequently triggered by the intrusion of hot primitive magma into a more evolved magma-chamber or -mush zone. During intrusion into the cooler mush zone, the basaltic magma undergoes crystallization, which in turn releases heat and volatiles to the mush. This should cause a drop in bulk mush-viscosity, potentially leading to its mobilization and even eruption. The non-linear changes in the transport properties of both magmas during this interaction modulate how the magmas accommodate deformation during both interaction and ascent. As such, this interaction represents a complex disequilibrium phenomenon, during which the material properties guiding the processes (dominantly viscosity) are in constant evolution. Such a scenario highlights the importance of non-isothermal sub-liquidus processes for the understanding of natural magmatic and volcanic systems and underlines the need for a rheological database to inform on, and to model, this interaction process. Here we present new experimental data on the disequilibrium rheology of the least evolved end-member known to be involved in magma mixing and eruption triggering as well as lava flow processes in the Phlegrean volcanic district (PVD). We measure the melt´s subliquidus rheological evolution as a function of oxygen fugacity and cooling rate and map systematic shifts in its rheological “cut off temperature; Tcutoff” (i.e. the point where flow ceases). The data show that 1) the rheological evolution and solidification behavior both depend on the imposed cooling-rate, 2) decreasing oxygen fugacity decreases the temperature at which the crystallization onset occurs and modifies the kinetics of melt crystallization and 3) the crystallization kinetics produced under dynamic cooling are significantly different than those observed at or near equilibrium conditions. Based on the experimental data we derive empirical relationships between the environmental parameters and Tcutoff. These empirical descriptions of solidification and flow may be employed in numerical models aiming to model lava flow emplacement or to reconstruct the thermomechanical interaction between basalts and magma mush systems. We further use the experimental data in concert with models of particle suspension rheology to derive the disequilibrium crystallization kinetics of the melt and its transition from crystallization to glass formation.